Medication and psychotherapy in eating disorders: is there a gap between research and practice?. Issue 1 (December 2015) - Cooper, Myra; Kelland, Hannah
Abstract Background Little research has investigated the use of evidence-based guidelines by eating disorder (ED) therapists, or prescribing of psychotropic medication. Moreover, people with EDs have rarely been surveyed on these topics, and their clinical and demographic features have not been presented. This study investigated perception of psychotherapy, psychotropic medication and the clinical characteristics of a community sample of people with EDs. Method An online survey methodology was used to recruit 253 people with eating disorders in the community. Where feasible, comparisons were made between four types of eating disorder, anorexia nervosa, bulimia nervosa, and two types of atypical or 'sub-threshold' eating disorder. Results Unlike medication, reported psychotherapy showed some congruence with evidence based and other guidance. Most participants were currently receiving either psychotherapy, medication or both, and most had a severe and chronic ED. Conclusions Findings are considered in light of use of evidence-based treatment for EDs, calls for greater dissemination of cognitive behaviour therapy (CBT); indications that much may be poor quality; and the importance of what treatments to offer those who are chronically and severely ill. Development of theory and novel treatments is considered a priority.